The location of shrimp ponds in several areas of indonesia and their problems (Indonesia, 1992)
This is the first working paper from AADCP component 1, which is much welcomed. It deals with a major topic of the component and is of relevance to all Asean countries.
Keywords: Shrimp culture,Nuôi tôm